Interpersonal Relations in Swedish Linguistic Culture through the Prism of Stable Similes (in Background of the Russian Language) - A. S. Alyoshin (Научный диалог, 2017)
The results of the analysis of stable similes of the Swedish language that characterize interpersonal relationships are presented. The purpose of this article is to reveal the national identity of the ways of expressing ideas about interpersonal relationships in the Swedish linguistic culture. Material for the study consists of expressions extracted from phraseological dictionaries of Swedish language; texts from Swedish literature and journalism, including the analyzed lexical units; the results of a survey of native speakers of the Swedish language, as well as data of the dictionaries of sustainable similes of the Russian language. Analysis of the Swedish phraseology is made against the corresponding fragment of the language picture of the world in Russian linguistic culture. The relevance and novelty of research is caused by absence at the moment of large-scale studies devoted to the analysis of Swedish stable similes in linguistic and cultural aspect, as well as the lack of the dictionary of Swedish stable similes and Russian-Swedish dictionary of stable similes. In the result of the analysis it can be stated that the ideographic field of stable similes of the Swedish language is significantly different in composition from the corresponding field in the Russian language. The linguistic facts of only three ideographic groups in this field have full or partial Russian equivalents. Units of other groups of considered field require detailed linguistic and cultural, and in some cases historical and etymological review when submitting them to the Russian-speaking audience.